Evaluation of polypropylene based composites from thermal effects developing under cyclic bending tests. (15th December 2017) - Boccardi, Simone; Carlomagno, Giovanni Maria; Meola, Carosena; Russo, Pietro; Simeoli, Giorgio
Abstract: The attention of this work is driven towards the investigation of thermoplastic composite materials, based on a polypropylene matrix, which may be neat, or modified by the addition of a relatively low amount of a specific compatibilizing agent, and reinforced with glass or jute fibres. These materials specimens are subjected to cyclic bending tests while infrared thermography is exploited to monitoring thermal effects coupled with tension/compression stresses. The obtained results show that through visualization and measurement of the small temperature variations it is possible to help to increase knowledge about this type of composite materials. In fact, it is largely established that macromolecular interactions and interfacial micromechanics effects (e.g., frictional sliding) in composite systems are dependent on multiple physical chemical factors, in particular on temperature, which are related not only to the nature of the constituent materials but also to the process conditions to obtain the same. Therefore, the visualized thermal effects may provide a minor but useful contribution to gain more insights into the above mentioned aspects.